2019
DOI: 10.12688/wellcomeopenres.15100.2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of using primaquine without prior G6PD testing: a case series describing the obstacles to the medical management of haemolysis

Abstract: Radical cure of Plasmodium vivax malaria in glucose-6-phosphate dehydrogenase (G6PD) deficient individuals employs weekly primaquine dosing. This is the only recommended regimen for this patient sub-group. If national malaria programs mandate daily primaquine dosing (the recommended regimen for G6PD normal individuals), then G6PD testing before prescription is necessary to avoid iatrogenic haemolysis in G6PD deficient individuals. In this case series, two P. vivax infected patients with unknown G6PD status fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Thus, our findings indicate that phenotypic testing alone may not be enough to detect G6PD deficiency, even in hemizygous male individuals. Similar incidents have previously been reported in which individuals carrying the Mahidol mutation were classified as G6PD normal by phenotypic tests ( Chu et al, 2017 ; Chu et al, 2019 ). People carrying other G6PD variants (G6PD Santa Maria, G6PD A − , G6PD Viangchan, G6PD Gaohe, G6PD Chinese 4, G6PD Chinese 5, G6PD Canton and G6PD Kaiping) were also found to have enzyme activity levels of greater than 30% ( Powers et al, 2018 ; He et al, 2020 ; Boonyuen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, our findings indicate that phenotypic testing alone may not be enough to detect G6PD deficiency, even in hemizygous male individuals. Similar incidents have previously been reported in which individuals carrying the Mahidol mutation were classified as G6PD normal by phenotypic tests ( Chu et al, 2017 ; Chu et al, 2019 ). People carrying other G6PD variants (G6PD Santa Maria, G6PD A − , G6PD Viangchan, G6PD Gaohe, G6PD Chinese 4, G6PD Chinese 5, G6PD Canton and G6PD Kaiping) were also found to have enzyme activity levels of greater than 30% ( Powers et al, 2018 ; He et al, 2020 ; Boonyuen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…Qualitative G6PD screening prior to PART applying low-dose primaquine (0�25mg/kg/d x 14d) may be viewed as adequately safe for females because the prolonged dosing allows mitigation of potential harm by cessation of therapy after the onset of symptoms of acute hemolytic anemia. However, that onset occurs late and abruptly; typically, a day after the 3 rd or 4 th dose with a sudden drop of hemoglobin accompanied by haemoglobinuria and jaundice, i.e., with hemolytic crisis in progress [36,37]. There is no validated means of monitoring for those events in averting serious harm, i.e., specification of any specific clinical or laboratory parameter at a designated time point during treatment reliably indicating cessation of treatment before serious harm is done.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Even with the correct dose, intravascular hemolysis in male with G6PD Mahidol variant can occur [50]. It has been demonstrated that the G6PD Viangchan and Mahidol, the most common variants observed in southern Thailand, cause low enzymatic activity in RBCs and risk for acute hemolysis induced by PQ [51,52].…”
Section: Discussionmentioning
confidence: 99%